Membangun Paradigma Ilmu Pendidikan Islam: Kajian Ontologi, Epistemologi dan Aksiologi - Khojir Khojir (Dinamika Ilmu, 2011)
Islamic education as a science faces a pull of the study of dogmatic theological or philosophical studies. So there is an assumption that the study of Islamic education has been adopting Western philosophy and then looked for justification in Qur’an. From this background, it is necessary to the existence of thought that led to the paradigm of Islamic education as a science from the perspective of ontology, epistemology and axiology. In the study of ontology that Islamic education should have a separate study area with a distinctive style of Islamic education that differentiates it from other sciences such as human, educational function, the purpose of education, education curriculum, students, teachers, teaching methods and approaches, and evaluation based on the teachings of Islam. From the aspect of educational epistemology of Islam must have a way to explore and test the truth of such examining values of Islamic education in a philosophical ideal that exists in the Qur'an and the Hadith as well as empirical studies through pragmatic. The level of educational paradigm axiology as a science should have a value associated benefits and goals such as building science to human welfare, educating and directing humans towards awareness of God, and has the social and vocational skills.